2013
DOI: 10.1186/1475-2875-12-79
|View full text |Cite
|
Sign up to set email alerts
|

A controlled, parallel, cluster-randomized trial of community-wide screening and treatment of asymptomatic carriers of Plasmodium falciparum in Burkina Faso

Abstract: BackgroundIn malaria-endemic countries, large proportions of infected individuals are asymptomatic, constituting a reservoir of parasites for infection of newly hatched mosquitoes. This study evaluated the impact of screening and treatment of asymptomatic carriers of Plasmodium falciparum.MethodsEighteen villages were randomized (1:1) to study arms and inhabitants participated in four community screening campaigns: three before the rainy season ~1 month apart, and the fourth after the rains at ~12 months. On d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
127
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(134 citation statements)
references
References 23 publications
5
127
2
Order By: Relevance
“…Large areas of southern and eastern Africa have EIR values below 4, indicating that repeated MSAT programmes with a high-sensitivity diagnostic test of the order of 2 parasites per microlitre could be considered as an intervention in these areas 43 . However, the EIR in Burkina Faso is much higher than 4, suggesting that MSAT would not be effective even with a highly sensitive diagnostic test (as confirmed in a recent trial 17,18 ). Equally, using a higher sensitivity diagnostic could reduce the number of treatment rounds required to interrupt transmission, thus reducing the operational and financial requirements and potentially increasing the community acceptance of the intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large areas of southern and eastern Africa have EIR values below 4, indicating that repeated MSAT programmes with a high-sensitivity diagnostic test of the order of 2 parasites per microlitre could be considered as an intervention in these areas 43 . However, the EIR in Burkina Faso is much higher than 4, suggesting that MSAT would not be effective even with a highly sensitive diagnostic test (as confirmed in a recent trial 17,18 ). Equally, using a higher sensitivity diagnostic could reduce the number of treatment rounds required to interrupt transmission, thus reducing the operational and financial requirements and potentially increasing the community acceptance of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Two recent MSAT trials, which used RDT screening to identify infections, failed to lead to a sustained reduction in malaria parasite prevalence or disease incidence 17,18 . It has been suggested that this could be at least partly due to ongoing transmission from low-density infections that were undetectable by the RDT or by microscopy.…”
Section: S95mentioning
confidence: 99%
“…18 On the other hand, a recent trial in Burkina Faso indicated no impact of IST on community-wide malaria transmission. 27 Further studies are ongoing to test whether school children can be used to detect and monitor malaria "hotpots" within a community, where localized transmission and re-infection rates are high. This could, in turn, trigger intensive hotspot-focused community interventions to interrupt malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Hence in this trial, information is collected about the number of sexual contacts that occur with residents of villages outside that of the index subject. Regardless of distance between clusters, if a fraction of the exposures among subjects in the treatment clusters come from outside the cluster the estimate of the randomized treatment effect of an infectious disease prevention strategy will be attenuated compared to what it would have been had the treatment been implemented throughout the population of interest (Tiono et al 2013;Wang et al 2014).…”
Section: Introductionmentioning
confidence: 99%